"Better Too Much Than Not Enough": The Nomination of Women of Color to the Federal Bench. (3rd July 2022) - Moyer, Laura; Harris, Allison P.; Solberg, Rorie Spill
ABSTRACT: It is well established that the federal judiciary has been an overwhelmingly White and male institution since its creation and continues to be so today. Even as presidents of both parties have looked to diversify their judicial nominees, this has tended to result in the appointment of White women and men of color rather than women of color. Using data on the confirmed federal district and circuit court judges from presidents Clinton through Trump, we assess how the backgrounds of women of color nominated to the federal judiciary compare with those of other appointees. The results indicate that, compared to White male judges, women of color judges accrue more types of professional experience before their appointments, are more likely to have had prior experience as a judge, and are generally nominated earlier in their careers.